(untitled) (diségno, 2022)
Designing a typeface implies the search for a visual coherence between a series of shapes with different structures. This coherence is the effect of different interdependent factors that can be described and measured. The purpose of this analysis is to provide a detailed description of some of the main independent variables of the design of a typeface and their interactions. We will then present a study of the shape relationships between the glyphs of a typeface, we will identify some of the design variables of a typeface, we will give a description of these relations and use all these notions as a design and teaching tool. This approach is inspired by the work of Donald Knuth and therefore has its roots in digital typeface design and can lead to a parametric approach to drawing. Isolating the independent variables allows us to control the design choices and potentially to experimentally verify their effects. A detailed description also allows us to control through the study of functions the interpolations between shapes – a widespread practice since the 1990s to draw intermediate variants of typefaces. In this manuscript we will consider the shape of the glyphs intended as silhouettes, even if described by the outlines; therefore we will consider the impact of the perceptual interaction between black and white on the basic design variables.From an educational point of view, elaborating and verifying the effects of a variable and checking an interpolation, in addition to providing specific knowledge for the typography field, can be placed among the configuration exercises in the context of basic design. This method has been used at some courses of design in some Italian universities.